Reading the Bible in Islamic context: Qurʼanic conversations - Crowther, Daniel J.; Shafaie, Shirin; Glaser, Ida; Akhtar, Shabbir (Routledge reading the Bible in Islamic context series, 2018)
Biblical interpretation in Islamic context: particular experiments, general tasks, signposts for the future / Ida Glaser -- Abraham in narrative worldviews: reflections on doing comparative theology through Christian-Muslim dialogue in Turkey / George Bristow -- Toward inter-theological hermeneutics: a case study in reading between the Joseph stories / Shirin Shafaie -- The "sin" of David in the light of Islamic thought / Ali Makhlabi and Larry Ciccarelli -- David and the single ewe lamb: tracking conversation between two texts (2 Samuel 12:3 and Q38:23) when they are read in their canonical contexts / Carol Walker -- Facing mirrors: the intertwined golden calf story / Mohammad Ghandehari and Mohsen Feyzbakhsh -- The fourth source: Israʼiliyyat and the use of the Bible in Muslim scholarship / Wan Mohd Fazrul Azdi Wan Razali, Ahmad Yunus Mohd Noor and Jaffary Awang -- Constrained by scriptural polemics: Hamiduddin Farahi on the akedah / Nazirudin Mohd Nasir -- The culture shock of the Bible / Danny Crowther -- Islamic tradition and the reception history of the Bible / Martin O'Kane and Talha Bhamji -- The morphology of the narrative exegesis of the Qurʼan: the case of the cow of the Banu Israʼil (Q2:67-74) / Ali Aghaie -- The place of purity in faith / Dwight Swanson -- Biblical Ruth as a Qurʼanic Queen of Sheba: scriptural narratives of foreigner assent / Georgina Jardim -- Reading Paul on idolatry (Romans 1:18-32) alongside the Qurʼan: a theology of divine signs / Michael Lodahl -- Indirection in Biblical and Qurʼanic discourses, and in Bible translation in Islamic contexts / Andy Warren-Rothlin -- The Gospel of John as a structure for Muslim-Christian understanding / Dan Madigan -- Three methods for a Muslim reading of the Bible / Shabbir Akhtar